Pharmacological intervention of the FGF-PTH axis as a potential therapeutic for craniofacial ciliopathies - Christian Louis Bonatto Paese; Ching-Fang Chang; Daniela Kristeková; Samantha A. Brugmann (The Company of Biologists, 2022)
Ciliopathies represent a disease class characterized by a broad range of phenotypes including polycystic kidneys and skeletal anomalies. Ciliopathic skeletal phenotypes are among the most common and most difficult to treat due to a poor understanding of the pathological mechanisms leading to disease. Using an avian model (talpid2) for a human ciliopathy with both kidney and skeletal anomalies (orofaciodigital syndrome 14), we identified disruptions in the FGF23-PTH axis that resulted in reduced calcium uptake in the developing mandible and subsequent micrognathia. Although pharmacological intervention with the U.S. Food and Drug Administration (FDA)-approved pan-FGFR inhibitor AZD4547 alone rescued expression of the FGF target SPRY2, it did not significantly rescue micrognathia. In contrast, treatment with a cocktail of AZD4547 and teriparatide acetate, a PTH agonist and FDA-approved treatment for osteoporosis, resulted in molecular, cellular and phenotypic rescue of ciliopathic micrognathia in talpid2 mutants. Together, these data provide novel insight into pathological molecular mechanisms associated with ciliopathic skeletal phenotypes and a potential therapeutic strategy for a pleiotropic disease class with limited to no treatment options.